Sagarana, um livro de dois mundos / Sagarana, a book of two worlds - Santos, Lívia Ferreira (Revista de Letras, 2007)
O artigo objetiva dar conta de uma releitura de Sagarana, o primeiro livro de contos publicados por Guimarães Rosa, 1946. Propõe-se demonstrar como a obra se revela uma poderosa orquestração de inúmeros materiais originários de terra natal do Autor, Minas Gerais, Brasil. Mostra-se como, por meio de seu talento artístico, ele recria litariamente fatos da vida humana rústica, fenômenos naturais daquela região, assim como visões-de-mundo peculiares à gente do sertão. O autor obtem pleno êxito ao apresentar ao leitor, surpreendentemente, o conjunto focalizado, mediante o emprego de ma linguagem personalíssima. Por acréscimo, esboça-se uma breve analise de cada conto.The essay aims at revisiting Sagarana, the book of short-stories published by Guimarães Rosa in 1946. One tries to demonstrate how the composition of Sagarana reveals itself as being a powerful orchestration of numberless materials taken from the Author’s native land, Minas Gerais, Brazil. We also intend to show how the writer, by means of his artistic talent, is able to recreate facts of the rustic human life and natural phenomena of that region, as well as visions of the word peculiar to backwoods people, in a specially literary way. One tries to demonstrate how the Author is successful in presenting the whole surprisingly to the reader, by using sort of language almost of his own. In addition to that, a brief analysis of each short-story is outlined.